2017
DOI: 10.15244/pjoes/70178
|View full text |Cite
|
Sign up to set email alerts
|

Indicator-Based Assessment for Soil Resource Management in the Wrocław Larger Urban Zone of Poland

Abstract: This article presents a discussion about the issue of soil resource management in the context of sustainable development. These resources are one of the basic resources on Earth, conditioning the sustainable development of present and future generations by providing the capacity for food production. The study contains an indicator-based assessment of changes in available soil resources as a result of progressive urbanization processes in the suburban area of a big city. The case study was the Wrocław Larger Ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…The latest research of EF and BC at national level showed, that Poland's BC per capita was 2.08 gha [62]. This means, that EF F of Wrocław is 46 [63]. The obtained differences could be connected with number of components taking into consideration in each research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest research of EF and BC at national level showed, that Poland's BC per capita was 2.08 gha [62]. This means, that EF F of Wrocław is 46 [63]. The obtained differences could be connected with number of components taking into consideration in each research.…”
Section: Discussionmentioning
confidence: 99%
“…The city is fast developing and has strongly spreading suburban zones (light blue on the map). The suburban zone of Wrocław consist of 10 municipalities and has a total surface area of 1416.4 km 2 [46]. Wrocław is one of the largest cities in Poland with approximately 638,000 inhabitants (according to data of Central Statistical Office of Poland, state as at 31 December 2016).…”
Section: Study Areamentioning
confidence: 99%
“…Wrocław is known as a strongly transforming city, with a very large residential and suburban area [58]. Suburbanization could be listed among the other problems the city is facing, such as the heat island [59] effect or air pollution [60].…”
Section: Wrocławmentioning
confidence: 99%
“…Other aspects that were studied were the environmental aspects and impacts of urban sprawl: land take and soil sealing [73,74], water consumption increase [75], surface water pollution from new traffic infrastructure [76], low emission and air pollution [77], potential of renewable energy production [78,79], landscape diversification and conversion [80,81], and changes in ecosystem benefits and services [82,83].…”
Section: Study Sitementioning
confidence: 99%